Reputation in the Digital Age: Strategies of Online Redemption after Peer-Exposed Mistakes - Ahmmed, Badhon; Hakobyan, Anahit (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study investigates how individuals navigate reputational challenges after peer-exposed mistakes in digital environments, with a focus on strategies of online redemption and long-term adaptations. Methods and Materials: A qualitative research design was employed to capture lived experiences and interpretive meanings associated with reputational repair. Data were collected through semi-structured interviews with 21 participants from Armenia, selected purposively to ensure diversity in gender, age, and professional background. Interviews lasted between 45 and 70 minutes, were audio-recorded with consent, and transcribed verbatim. Data collection continued until theoretical saturation was reached. Thematic analysis was conducted using NVivo 14 software, following iterative cycles of coding, categorization, and theme refinement. Reflexive memos and constant comparison techniques were used to enhance validity and minimize researcher bias. Findings: Three overarching themes were identified: (1) experiences of peer-exposed mistakes, including public humiliation, emotional distress, social identity erosion, digital permanence, cultural pressures, and peer power dynamics; (2) strategies of online redemption, encompassing apology, content management, humor, support-seeking, strategic silence, rebranding, and counter-narratives; and (3) long-term reflections and learning, which involved digital literacy growth, emotional resilience, restructured peer relations, ethical awareness, identity transformation, and future-oriented strategies. Conclusion: The study demonstrates that online redemption after peer-exposed mistakes is a dynamic and socially embedded process that combines discursive, relational, and strategic elements. Redemption strategies are influenced not only by digital tools but also by cultural contexts and peer dynamics.